1995
DOI: 10.1021/j100045a037
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Reaction Studies of Transient Nature of Adsorbates during NO-CO Reaction over Rh/SiO

Abstract: The transient nature of adsorbates for the reaction of NO with CO over a 4 wt % Rh/Si02 catalyst has been studied by in situ infrared spectroscopy combined with pulse transient techniques. Dynamic behavior of infrared-observable Rh-NO-, Rh-NO+, Rh+(CO)2, and linear and bridged CO reveals that dissociation of Rh-NO-oxidizes Rho to R h ' ; R h ' chemisorbs CO and NO as Rh+(C0)2 and Rh-NO', respectively; and Rh+(CO)* can either undergo reductive agglomeration or react with adsorbed oxygen to produce C02 at 473-52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The observed differences in the transient gas phase responses of NO, N 2 and N 2 O obtained at 250 and 450 °C, following the switch He → 1% NO/He (Figures and ), over Rh supported on TiO 2 and W 6+ -doped TiO 2 carriers can qualitatively be discussed with respect to the following sequence of elementary steps, which are based on results either obtained in this work or which have been reported in the literature. ,, Here, (S) is a site on the Rh surface. Assuming that the rate-determining step is that of NO dissociation (eq 6), as suggested by many investigators in the case of Rh catalysts, ,,, the higher initial yield of N 2 observed over the Rh/TiO 2 (W 6+ ) as compared to the Rh/TiO 2 catalyst can be attributed to either the higher initial surface coverage of adsorbed NO, or to the larger value of the rate constant, k 2 , associated with this step, or to both. FTIR results obtained after 20 min of reaction with 1% NO/He mixture at 450 °C, followed by Ar treatment at 450 °C, revealed that the Rh−NO + species (the only kind of adsorbed NO species existing, 1920 cm -1 ) disappear very fast in Ar flow at 450 °C over the Rh/TiO 2 catalyst, while they persist even after 10 min of Ar purge in the case of Rh/TiO 2 (W 6+ ) catalyst.…”
Section: Discussionmentioning
confidence: 92%
“…The observed differences in the transient gas phase responses of NO, N 2 and N 2 O obtained at 250 and 450 °C, following the switch He → 1% NO/He (Figures and ), over Rh supported on TiO 2 and W 6+ -doped TiO 2 carriers can qualitatively be discussed with respect to the following sequence of elementary steps, which are based on results either obtained in this work or which have been reported in the literature. ,, Here, (S) is a site on the Rh surface. Assuming that the rate-determining step is that of NO dissociation (eq 6), as suggested by many investigators in the case of Rh catalysts, ,,, the higher initial yield of N 2 observed over the Rh/TiO 2 (W 6+ ) as compared to the Rh/TiO 2 catalyst can be attributed to either the higher initial surface coverage of adsorbed NO, or to the larger value of the rate constant, k 2 , associated with this step, or to both. FTIR results obtained after 20 min of reaction with 1% NO/He mixture at 450 °C, followed by Ar treatment at 450 °C, revealed that the Rh−NO + species (the only kind of adsorbed NO species existing, 1920 cm -1 ) disappear very fast in Ar flow at 450 °C over the Rh/TiO 2 catalyst, while they persist even after 10 min of Ar purge in the case of Rh/TiO 2 (W 6+ ) catalyst.…”
Section: Discussionmentioning
confidence: 92%
“…This band is associable with the formation of Rh(NCO) [40][41][42] species and rapidly disappears after the switch back to oxidising conditions, in tandem with the other carbonyls species, and concomitant with a burst of CO 2 production.…”
Section: Dispersive Exafs Of Ca 1 Wt% Rh/al 2 Omentioning
confidence: 96%
“…A number of the NO-CO reaction studies on Rh/SiO 2 catalysts have revealed that the reaction pathway for N 2 and CO 2 formation below light-off temperature is different from those above light-off [13,17]. Tables 2A and 2B list both reaction pathways.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Under such conditions, CO adsorbs on Rh + sites as Rh + (CO) 2 and NO adsorbs as Rh-NO -; the surface of supported Rh catalyst contains both Rh 0 and Rh + sites [13,17]. Increase in reaction temperature allows NO dissociation to occur.…”
Section: Reaction Mechanismmentioning
confidence: 99%